1994
DOI: 10.1042/cs0860149
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine β-Hydroxylase Immunoreactivity in Human Cerebrospinal Fluid: Properties, Relationship to Central Noradrenergic Neuronal Activity and Variation in Parkinson's Disease and Congenital Dopamine β-Hydroxylase Deficiency

Abstract: 1. Dopamine beta-hydroxylase is stored and released with catecholamines by exocytosis from secretory vesicles in noradrenergic neurons and chromaffin cells. Although dopamine beta-hydroxylase enzymic activity is measurable in cerebrospinal fluid, such activity is unstable, and its relationship to central noradrenergic neuronal activity in humans is not clearly established. To explore the significance of cerebrospinal fluid dopamine beta-hydroxylase, we applied a homologous human dopamine beta-hydroxylase radio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 0 publications
0
32
0
Order By: Relevance
“…In either body fluid, enzyme activity and protein level are strongly correlated, and essentially reflect the same biochemical phenotype. [14][15][16] Thus, we refer here to D␤H enzyme activity and D␤H protein levels interchangeably as D␤H levels.…”
Section: Evidence For Genetic Influences On Vulnerability To Drug-indmentioning
confidence: 99%
“…In either body fluid, enzyme activity and protein level are strongly correlated, and essentially reflect the same biochemical phenotype. [14][15][16] Thus, we refer here to D␤H enzyme activity and D␤H protein levels interchangeably as D␤H levels.…”
Section: Evidence For Genetic Influences On Vulnerability To Drug-indmentioning
confidence: 99%
“…4, 5, and 9), cerebrospinal fluid (radioimmunoassay; see Ref. 9), and sympathetic fibers (immunocytochemistry; see Ref. 10).…”
Section: Norepinephrine (Ne)mentioning
confidence: 99%
“…In a recent genome-wide association study (GWAS), rs7040170 was identified as one of the SNPs significantly associated with plasma DβH activity ( p = 1.31×10 -14 ) (Mustapic et al, 2014). Specifically, the G allele is associated with higher plasma DβH activity and correlated with higher DβH activity in cerebrospinal fluid (CSF) (O'Connor et al, 1994). DβH is expressed early in embryonic development (Yew et al, 1995) and increases in late gestation, and may influence the cortical surface area through its roles in cell proliferation, migration and differentiation (Tiu et al, 2003).…”
mentioning
confidence: 99%